Eleventh Five Year Plan 2007-2012 and Annual Plan 2007-2008 ( Draft) Volume-1 - Planning Commission (Planning Commission, 2007)
Since the state of Kerala came into being in 1956, it has witnessed a remarkable process of social and economic transformation. The essence of this process has been an erosion of its feudal and semi-feudal structures through government intervention, buttressed by mass movements, via crucial measures like land reforms, and a range of welfare programmes for the poor which are without parallel within India and even over much of the third world. The erosion of these enveloping feudal and semi-feudal structures has removed the fetters upon the underlying system of petty production, which is pervasive in Kerala and accounts for nearly 92 percent of the total work-force (in the so-called “unorganized sector”). This sector of petty and small-scale production constitutes the backbone of the state’s economy.
State Planning Board Thiruvananthapuram Government of Kerala